The effect of the presence of obstacles on the dynamic response of single-degree-of-freedom systems: Study of the scenarios aimed at vibration control. (4th August 2022) - Stefani, Giulia; De Angelis, Maurizio; Andreaus, Ugo
Abstract: In this paper, the effect of the presence of (existing or newly added) deformable and dissipative obstacles (bumpers) on the nonlinear dynamic response of a single-degree-of-freedom system, is investigated via parametric numerical analyses. Through the study of possible response scenarios which can occur by varying the bumpers' parameters (i.e., the position, the stiffness, and the damping, respectively) it is observed that the presence of the bumpers is not always unfavorable compared to the free flight condition. By properly selecting the bumpers' parameters it is possible to exploit the occurrence of impacts with beneficial effects. Furthermore, a relationship between the stiffness and the damping parameters of the bumpers, which allows to minimize the maximum value of the mass acceleration in primary resonance condition, is identified and discussed. Although this study is inspired by the practical problem of large horizontal displacements in base-isolated structures, it has a transversal nature with respect to different disciplinary fields. Consequently, the results obtained in this work can be extended also to further applications related to vibro-impact dynamics. Highlights: The occurrence of impact can significantly modify the response of SDOF systems. The study of the scenarios is functional to identify suitable control strategies. It is possible to exploit the occurrence of impact with beneficial effects. A unit value of the relaxation time allows to minimize the peak mass acceleration. Very small gaps involve an increasing reduction of the linear isolation frequency range.